The Advantages And Disadvantages Of Moving The Capital City Of Indonesia (Equal Development Or Destruction Of Land?) - Susilawati Susilawati*; Ramadha Yanti Parinduri; Wuri Astamala Dewi; Achmad Zahruddin; Suyanto Suyanto (Universitas Syiah Kuala, 2023)
The relocation of the Indonesian capital city is based on several aspects which include geographical aspects, increasing investment, increasing GDP, improving the quality of local products, and so on. However, this policy also has the potential to cause a number of losses such as land destruction, addition to state debt, corruption, and so on. Therefore, this study aims to analyze the pros and cons of moving the capital city of Indonesia. This research is a qualitative research with a descriptive approach using the literature method in collecting data using the SWOT method in data analysis. From the advantages of these losses, the researcher has the view that the policy of relocating the Indonesian state capital can still be carried out by paying attention to environmental aspects, budget efficiency, and monitoring aspects so that all potential losses can be minimized to a minimum.